218k views
1 vote
Y = – 8x — 49
y= -x
Solve the system by subsitiution

2 Answers

6 votes
Y= -7
X= 7
7, -7
Or however
User Kiduxa
by
5.2k points
2 votes

Answer:


x=7


y=-7

or


(7,-7)

Explanation:


y = -8x-49\\y=-x

Begin by substituting
-x for
y in the first equation given:


-x=-8x-49

Add
8x to both sides of the equation:


-7x=49

Divide both sides of the equation by the coefficient of
x, which is
-7:


x=7

Now, substitute the
x value into the second equation given:


y=-(7)

Distribute the negative:


y=-7

-

You can check your work by substituting the solved values into one of the given equations. Let's use the second one, as it will be easier to work with:


y=-x


-7=-(7)


-7=-7

Since the sides of the equation are equal to each other, our solution is correct!

User WizLiz
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.